Heidegger and Hegel: Distance and Proximity - Dastur, Francoise (1996)
Not being a mere epigonenor disprover ofHegel, Heidegger started a dialogue with Hegel's thought since his Habilitation thesis in 1915 until his last reference to Hegel in 1969. This brief paper intends to point out Heidegger' s ambivalent relationship to Hegel in three fundamental issues in which his agreementis as important as his disagreement: the relationship between being and thought, the identity of being and nothingness, the conception of history. Light is thus shed upon the oppositions between the speculative sentence and the phenomenological tautology, between the oppositional logic and the ontological difference, and between the dialectics of history and the meditation on the history of being and Ereignis.